Right ventricular epicardial arrhythmogenic substrate in long-QT syndrome patients at risk of sudden death. Issue 3 (5th January 2023) - Pappone, Carlo; Ciconte, Giuseppe; Anastasia, Luigi; Gaita, Fiorenzo; Grant, Edward; Micaglio, Emanuele; Locati, Emanuela T; Calovic, Zarko; Vicedomini, Gabriele; Santinelli, Vincenzo
Abstract: Aims: The long-QT syndrome (LQTS) represents a leading cause of sudden cardiac death (SCD). The aim of this study was to assess the presence of an underlying electroanatomical arrhythmogenic substrate in high-risk LQTS patients. Methods and results: The present study enrolled 11 consecutive LQTS patients who had experienced frequent implantable cardioverter-defibrillator (ICD discharges triggered by ventricular fibrillation (VF). We acquired electroanatomical biventricular maps of both endo and epicardial regions for all patients and analyzed electrograms sampled from several myocardial regions. Abnormal electrical activities were targeted and eliminated by the means of radiofrequency catheter ablation. VF episodes caused a median of four ICD discharges in eleven patients (6 male, 54.5%; mean age 44.0 ± 7.8 years, range 22–53) prior to our mapping and ablation procedures. The average QTc interval was 500.0 ± 30.2 ms. Endo-epicardial biventricular maps displayed abnormally fragmented, low-voltage (0.9 ± 0.2 mV) and prolonged electrograms (89.9 ± 24.1 ms) exclusively localized in the right ventricular epicardium. We found electrical abnormalities extending over a mean epicardial area of 15.7 ± 3.1 cm 2 . Catheter ablation of the abnormal epicardial area completely suppressed malignant arrhythmias over a mean 12 months of follow-up (median VF episodes before vs. after ablation, 4 vs. 0; P = 0.003). After the procedure, the QTc interval measured in a 12-lead ECG analysis shortened to a mean of 461.8 ± 23.6 ms ( P = 0.004). Conclusion: This study reveals that, among high-risk LQTS patients, regions localized in the epicardium of the right ventricle harbour structural electrophysiological abnormalities. Elimination of these abnormal electrical activities successfully prevented malignant ventricular arrhythmia recurrences.